Preparation of quaternary compounds Cu₂ZnSnS₄ by using the self-propagating high-temperature synthesis - Bacherikov, Yu.Yu.; Mirzayev, M.N.; Zhuk, A.G.; Okhrimenko, O.B.; Doroshkevich, N.V.; Kidalov, V.V.; Goroneskul, V.Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2021)
The possibility of preparing finely dispersed Cu₂ZnSnS₄ by using the method of self-propagating high-temperature synthesis has been studied in this work. Investigations of Raman scattering and IR-Fourier spectroscopy of the synthesized finely dispersed material have been carried out. The analysis of the Raman and IR-Fourier spectra showed that the synthesized material in the process of preparation is formed with a kesterite structure with the inclusion of a certain amount of secondary phases in the form of sulfides and stannites. У роботі досліджена можливість отримання дрібнодисперсного Cu₂ZnSnS₄ методом самопоширюваного високотемпературного синтезу. Проведено дослідження комбінаційного розсіювання світла та ІЧ-Фур’є-спектроскопії синтезованого дрібнодисперсного матеріалу. Аналіз спектрів КР та ІЧ-Фур’є показав, що синтезований матеріал у процесі отримання формується зі структурою кестериту із включенням деякої кількості вторинних фаз у вигляді сульфідів та станитів.